Analysis of Psychosocial Hazard Potential and Its Implications on the Occupational Safety and Health Performance of Employees in the QC Department of PT Garudafood Putra Putri Jaya, Tbk : Analisis Potensi Bahaya Psikososial dan Implikasinya terhadap Kinerja K3 Karyawan Departemen QC PT Garudafood Putra Putri Jaya, Tbk - Moch Akeyla Anugrah; Okik Hendriyanto Cahyonugroho (Media Ilmiah Teknik Lingkungan (MITL), 2026)
Because it can have an impact on employee performance, work stress is an important issue for businesses. The goal of this study is to assess the degree of stress using a straightforward random sampling technique. The Slovin formula and a 10% tolerance level are used to estimate the sample size. In accordance with the appendix to the Minister of Manpower Regulation (PERMENAKER) Number 5 of 2018 concerning Occupational Safety and Health in the Work Environment, a cross-sectional study was carried out using a quantitative approach with descriptive analysis. Respondents from the Quality Control (QC) department completed the questionnaire. Both the reliability and validity tests yielded reliable results. According to the study's findings, of the 44 responders to the questionnaire, 40 (90.91%) were classified as having mild stress and 4 (9.09%) as having moderate stress. The aforementioned rationale leads to the conclusion that workers in PT Garudafood Putra Putri Jaya, Tbk's Quality Control (QC) department are not overly stressed at work.